Carnegie International 1999-2000 : CI : 99- 00-V.01. - Armstrong, Richard; Crany, Jonathan; Fisher, Jean; Grynsztejn, Madeleine; McGuinn, Martin G.; Sassen, Saskia; Zizek, Slavoj (Pittsburgh : Carnegie Museum of Art Pittsburgh, 1999)
Ackermann, Franz ; Barney, Matthew ; Cardiff, Janet ; Currin, John ; Darboven, Hanne ; Demand, Thomas ; Dion, Mark ; Doherty, Willie ; Eliasson, Olafur ; Geers, Kendell ; Gonzalez-Torres, Felix ; Hamilton, Ann ; Hernández-Diez, José Antonio ; Huyghe, Pierre ; Katz, Alex ; Kentridge, William ; Kingelez, Bodys Isek ; Kinoshita, Suchan ; Kippenberger, Martin ; Marshall, Kerry James ; Murakami, Takashi ; Neshat, Shirin ; Neto, Ernesto ; Ofili, Chris ; Orozco, Gabriel ; Othová, Markéta ; Owens, Laura ; Ruscha, Edward ; Schneider, Gregor ; Sidén, Ann-Sofi ; Signer, Roman ; Sze, Sarah ; Taylor-Wood, Sam ; Tevet, Nahum ; Thater, Diana ; Tuymans, Luc ; Walker, Kara ; Wall, Jeff ; Wilson, Jane & Louise ; Chen Zhen
biografie
Engels
boek